1172. Mucormycosis Treated with Isavuconazole: A matched-Pair Analysis from the FungiScope® Registry. (31st December 2020) - Seidel, Danila; Cornely, Oliver; Vehreschild, Maria J G T; Koehler, Philipp; Salmanton-García, Jon; Klimko, Nikolay; Herbrecht, Raoul; Heinemann, Melina; Prattes, Jürgen; Schalk, Enrico; Miceli, Marisa H; Ráčil, Zdeněk; et al.
Abstract: Background: Isavuconazole (ISAV) is a novel, broad-spectrum triazole antifungal, available in both intravenous and oral formulations, for the treatment of adult patients with invasive aspergillosis or mucormycosis. In this retrospective case collection study, we compared outcomes for patients with invasive mucormycosis treated with ISAV versus other systemic antifungal therapies, in order to evaluate the real-world effectiveness of ISAV. Methods: Proven and probable invasive mucormycosis cases treated with ISAV for a minimum of four consecutive days between 2016 and 2019 were identified from the FungiScope ® registry. Matched controls were defined as patients treated with lipid formulations of amphotericin B (lipid-AMB), posaconazole, or a combination of both, as first-line therapy between 2011 and 2019. Case-matching criteria included disease severity, presence of hematological malignancy or allogeneic stem cell transplantation, and surgery for fungal disease. Baseline patient characteristics and clinical outcomes were compared descriptively. Results: Each of 30 ISAV cases was matched to 1–3 controls, including 25 ISAV cases each matched to 2 or 3 controls, which resulted in a total of 69 control cases. In 70.0% of ISAV cases (n=21), ISAV was administered as a treatment for invasive mucormycosis in patients who had received prior lipid-AMB. In the remaining cases, ISAV was administered after prior voriconazole treatment (n=3) or as first-line therapy (n=6). All control patients received either lipid-AMB, posaconazole, or a combination of both. Baseline demographic and clinical characteristics and causative pathogens were similar between ISAV cases and controls (Table). Overall response rates (defined as achieving a complete or partial response) at the final assessment were 50.0% (15/30) for ISAV cases and 50.7% (35/69) for controls. All-cause mortality was 43.3% (13/30) in ISAV cases as compared to 46.4% (32/69) in controls (Figure). Table. Demographic and clinical characteristics of 30 isavuconazole cases and 69 control cases Figure. Clinical response at final assessment and all cause mortality for 30 isavuconazole cases and 69 control cases Conclusion: In this retrospective analysis of cases from the FungiScope ® registry, patients with invasive mucormycosis showed similar overall treatment response and all-cause mortality rates with ISAV compared to treatment with lipid-AMB and/or posaconazole. These data support the effectiveness of isavuconazole in clinical practice. Disclosures: Danila Seidel, PhD, Basilea (Other Financial or Material Support, travel grant) Oliver Cornely, Prof., Actelion (Grant/Research Support)Actelion (Other Financial or Material Support, Personal fees)Al Jazeera Pharmaceuticals (Consultant)Allecra Therapeutics (Other Financial or Material Support, Personal fees)Amplyx (Other Financial or Material Support, Personal fees)Amplyx (Grant/Research Support)Astellas (Grant/Research Support)Astellas (Other Financial or Material Support, Personal fees)Basilea (Other Financial or Material Support, Personal fees)Basilea (Grant/Research Support)Biosys UK Limited (Other Financial or Material Support, Personal fees)Cidara (Other Financial or Material Support, Personal fees)Cidara (Grant/Research Support)Da Volterra (Grant/Research Support)Da Volterra (Other Financial or Material Support, Personal fees)Entasis (Other Financial or Material Support, Personal fees)F2G (Other Financial or Material Support)F2G (Grant/Research Support)Gilead (Grant/Research Support)Gilead (Other Financial or Material Support, Personal fees)Grupo Biotoscana (Other Financial or Material Support, Personal fees)Janssen Pharmaceuticals (Grant/Research Support)Matinas (Other Financial or Material Support, Personal fees)Medicines Company (Grant/Research Support)MedPace (Grant/Research Support)MedPace (Other Financial or Material Support, Personal fees)Melinta Therapeutics (Grant/Research Support)Menarini Ricerche (Other Financial or Material Support, Personal fees)Merck/MSD (Other Financial or Material Support, Personal fees)Merck/MSD (Grant/Research Support)Mylan Pharmaceuticals (Consultant)Nabriva Therapeutics (Other Financial or Material Support, Personal fees)Octapharma (Other Financial or Material Support, Personal fees)Paratek Pharmaceuticals (Other Financial or Material Support, Personal fees)Pfizer (Other Financial or Material Support, Personal fees)Pfizer (Grant/Research Support)PSI (Other Financial or Material Support, Personal fees)Rempex (Other Financial or Material Support, Personal fees)Roche Diagnostics (Other Financial or Material Support, Personal fees)Scynexis (Other Financial or Material Support, Personal fees)Scynexis (Grant/Research Support)Seres Therapeutics (Other Financial or Material Support, Personal fees)Tetraphase (Other Financial or Material Support, Personal fees) Philipp Koehler, MD, Akademie für Infektionsmedizin e.V., (Other Financial or Material Support, Personal fees)Astellas Pharma GmbH (Other Financial or Material Support, Personal fees)Cologne Excellence Cluster on Cellular Stress Responses in Aging-Associated Diseases, University of Cologne, Cologne, Germany (Other Financial or Material Support, Other)Gilead Sciences GmbH (Other Financial or Material Support, Personal fees)GPR Academy Ruesselsheim (Speaker's Bureau)Miltenyi Biotec GmbH (Other Financial or Material Support, Non-financial support)MSD Sharp & Dohme GmbH (Other Financial or Material Support, Personal fees)Noxxon N.V. (Speaker's Bureau)University Hospital, LMU Munich (Other Financial or Material Support, Personal fees) Nikolay Klimko, n/a, Astellas (Speaker's Bureau)Gilead (Speaker's Bureau)Merck/MSD (Speaker's Bureau)Pfizer (Speaker's Bureau) Marisa H. Miceli, MD, FIDSA, SCYNEXIS, Inc. (Advisor or Review Panel member) Martin Hoenigl, MD, SCYNEXIS, Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member) Farima Barmaki-Rad, n/a, Basilea Pharmaceutica International Ltd. (Employee) Mikael Saulay, n/a, Basilea Pharmaceutica International Ltd. (Employee) Marc Engelhardt, n/a, Basilea Pharmaceutica International Ltd. (Board Member, Consultant, Employee, Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Research Grant or Support, Shareholder, Speaker's Bureau, Independent Contractor, Other Financial or Material Support)Basilea Pharmaceutica International Ltd. (Employee) Kamal Hamed, n/a, Basilea Pharmaceutica International Ltd. (Employee)